Relative Educational Composition of the Female Population in Jordan for the Years 2010-2018 (Journal of Misan Researches, 2023)
The importance of the research lies in addressing an important and fundamental segment in the formation of society from multiple aspects, where the study focuses on the educational structure of females in Jordanian society, as the educational, cultural, and awareness level of women is reflected significantly at the level of society as a whole from various aspects. The study came to shed light on the educational composition of females in Jordan according to census data for the year (2010-2018). The study also focused on changes in the educational level starting from illiteracy to holders of a doctorate degree during that period at the level of the governorates of the Kingdom according to the social environment, the study consisted of two sections, the first of which dealt with the spatial variation of the educational structure according to each governorate in Jordan, while the second section dealt with the study of the spatial variation of the educational structure according to the environment (urban countryside), as well as the introduction and theoretical framework of the study. The study also came up with a set of conclusions, the most prominent of which was the decrease in illiteracy from (10.3%) in 2010 to (7.2%) in 2018. The study also showed an increase in females in the intermediate and advanced educational levels from (11.8, 0.3, 0.6, and 0.1%) for each of the bachelor's, higher diploma, master's, and doctoral levels respectively in 2010 to (17.0, 0.2, 0.9, 0.2%) in 2018 as well as the difference is clear by the environment, and the study developed a set of recommendations in this regard.